IDENTIFIKASI PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) SECARA MENYELURUH PADA UNIT PENGOLAHAN AIR MINUM DALAM KEMASAN (AMDK) DI PT. MAAN GHODAQO SHIDDIQ LESTARI JOMBANG JAWA TIMUR - , DANIS WIDIYANINGSIH, Fahrizal Yusuf Affandi., STP. M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Maan Ghodaqo Siddiq Lestari is an industry that produces bottled water in Tembelang Jombang East Java. The industry uses artesian springs as its main raw material. Production of bottled water in the PT. Maan Ghodaqo Siddiq Lestari through several stages of filtration and disinfection to water produced free from physical hazards, chemical, or biological. Implementation of GMP in the industry is needed to maintain the quality of the resulting product. Therefore, required an identification of GMP implementation so as to know the location and cause of deviations such deviations. GMP (Good Manufacturing Practices) is a good way of production and the right to produce a product that meets quality requirements and food safety. GMP implementation guidelines set out in the Rules of Ministry of Industry of the Republic of Indonesia Number 75/M-IND/PER/7/2010 on Guidelines How Processed Food Production (Good Manufacturing Practices) or more commonly referred to CPPOB 2010. This identification is done by comparing the actual conditions of production companies, especially in the room with the rules set forth in CPPOB 2010 using the identification of conformity and nonconformity accreditation forms. Results obtained are analyzed quantitatively by calculating the number of companies that fit the real condition and not fit. Problem solving is done by using a Pareto diagram and ishikawa. Based on the identification that has been done, there are six of 15 who deviate stale. Deviations are found in the aspect of location, building, sanitation facilities, process control, and maintenance employees and sanitation programs. Percentage of the overall suitability of 92.77%, while that does not conform of 7.23%. Scope of buildings which contribute the largest percentage deviation of 33.33%. This is due to four factors, namely human, methods, machines and the environment.